Comparative analysis of floristic richness and diversity in six central forest reserves of north eastern Uganda - Samuel Ojelel; Esther Katuura; Patrick Mucunguzi; James Kalema (BMC Ecology and Evolution)
Abstract As the extinction risk of plants increases globally, there is need to prioritize areas with high floristic richness and diversity to inform the design of evidence-based conservation interventions. As such, this study aimed to comparatively analyse floristic diversity in six central forest reserves (CFR) of north eastern Uganda. This was guided by two objectives namely; (i) to determine the floristic richness and diversity in the CFRs and (ii) to evaluate the similarity and complementarity of floristic composition. Data was collected from nested quadrats (20 × 20 m for trees, 10 × 10 m for shrubs and 5 × 5 m for herbaceous climbers, forbs and grasses) placed at intervals of 100 m along a transect of 1000 – 1500 m. Species richness, diversity and evenness were determined for each CFR. Binary similarity coefficients were computed because only presence/absence data of plant species was recorded. A sum of 417 plant species in 76 families were recorded representing 8.7% of known vascular plants reported in Uganda. The CFRs have significantly variable Shannon–Wiener diversity indices ranging from 4.2 in Kano CFR to 4.47 in Bululu hill CFR (t = 85.291, df = 4, p = 0.00). The CFRs cluster into two groups namely Onyurut and Ogera hills and Akur, Kano, Bululu hills and Mount Moroto. The lowest similarity index was between Ogera hills and Moumt Moroto CFRs (0.37 or 37%) while the highest was between Akur and Kano CFRs (0.63 or 63%). The CFRs complement one another by supporting plant species not recorded elsewhere with three CFRs (Bululu hills, Mount Moroto and Onyurut) accounting for 81.53% of the plant taxa. The CFRs in NE Uganda have richness and floristic diversity with up to 8.7% of the known plants in Uganda present. The conservation status of these species is Vulnerable (4), Near Threatened (4), Least Concern (137), Data Deficient (1) and Not Evaluated (271). The two similarity clusters depict variation in altitudinal, proximity and climatic conditions. Five CFRs are required to conserve 95% of the species recorded. Therefore, the CFRs investigated play a complementary role in conserving the floristic diversity in north eastern Uganda.